The Role of Profitability in Moderating the Relationship between Sustainability Reporting and ESG Disclosure onFirm Value of Energy Sector in Indonesia - Wulandari, Tri; Hani, Syafrida; Sari, Maya (Journal of Applied Accounting and Taxation, 2025)
This study aims to test and analyze the effects of Sustainability Reporting and ESG Disclosure on firm Value, moderated by profitability, among energy sector companies listed on the Indonesia Stock Exchange in 2019-2023. The research is associative and quantitative. The population of this study comprised 87 companies listed on the Indonesia Stock Exchange, which were purposively sampled, yielding 11 companies in the 2019-2023 period. The collected data were analyzed using SPSS version 27. The results of this study indicate that only Sustainability Reporting affects firm value, as measured by Price-to-Book Value (PBV). Then, Profitability as measured by ROA is also unable to moderate either Sustainability Reporting or ESG Disclosure on firm Value.